Prospects and challenges of utilizing sugarcane bagasse as a bio-coagulant precursor for water treatment - Kingsley O. Iwuozor; Adewale George Adeniyi; Ebuka Chizitere Emenike; Toluwalase Ojeyemi; Abel U. Egbemhenghe; Chika J. Okorie; Bridget Dunoi Ayoku; Oluwaseyi Damilare Saliu (Biotechnology Reports, 2023)
Sugarcane bagasse is an abundant and renewable agricultural waste material generated by the sugar industry worldwide. The use of sugarcane bagasse as a bio-coagulant precursor in water treatment is an eco-friendly and cost-effective approach that has shown great potential. This article reviewed the prospects and challenges of utilizing sugarcane bagasse as a bio-coagulant precursor for water treatment. The article reviewed past studies and explored the properties and chemical composition of sugarcane bagasse and the bioactive compounds that can be extracted from it, as well as their potential coagulation performance in water treatment. It was observed that there are few studies that have been published on the subject. The effectiveness of sugarcane bagasse-based coagulants varies depending on several factors, such as pH, temperature, and water quality parameters. However, the lack of standardization in the production of sugarcane bagasse-based coagulants is a challenge that needs to be addressed. Additionally, the optimization of extraction and processing methods to enhance the effectiveness of sugarcane bagasse-based coagulants needs to be investigated further. In conclusion, the use of sugarcane bagasse as a bio-coagulant precursor holds great promise for the future of sustainable water treatment. The potential for sugarcane bagasse to be used as a bio-coagulant precursor highlights the importance of exploring alternative and sustainable materials for water treatment.